2023
DOI: 10.1097/md.0000000000034292
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of sarcopenic visceral obesity in hepatocellular carcinoma treated with TACE

Abstract: Although Transartial chemoembolization (TACE) is one of the recommended treatments for hepatocellular carcinoma (HCC), there is always a dispute on the selection of the best beneficiary for treatment. We studied the prognostic value of nutritional markers, obesity, visceral obesity and sarcopenia on survival outcomes under single and different combinations. In a retrospective cohort of 235 patients with HCC at different stages, more accurate comprehensive prognostic factors were obtained by combining and compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Of the 12 studies included [13][14][15][16][17][18][19][20][21][22][23][24], eight were from Asian countries [13,15,17,19,[21][22][23][24], and four were from non-Asian countries [14,16,18,20]. In terms of treatment options, nine studies utilized TACE [13,15,17,[19][20][21][22][23][24], two employed TAE [14,18], and one applied TARE [16]. Previous studies have employed different muscle mass measurements.…”
Section: Study Descriptionmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the 12 studies included [13][14][15][16][17][18][19][20][21][22][23][24], eight were from Asian countries [13,15,17,19,[21][22][23][24], and four were from non-Asian countries [14,16,18,20]. In terms of treatment options, nine studies utilized TACE [13,15,17,[19][20][21][22][23][24], two employed TAE [14,18], and one applied TARE [16]. Previous studies have employed different muscle mass measurements.…”
Section: Study Descriptionmentioning
confidence: 99%
“…One study reported both SMI and PMI; considering the study's main result, we included the PMI data into the meta-analysis [22]. Seven records used the SMI [17][18][19][20][21]23,24], two used the PMI [13,15], and two used the FFMA [14,16]. The median observation period was five years (range: 3.3-16.7 years).…”
Section: Study Descriptionmentioning
confidence: 99%
See 3 more Smart Citations